2020
DOI: 10.1021/jacs.9b13722
|View full text |Cite
|
Sign up to set email alerts
|

Protecting-Group-Free Syntheses of ent-Kaurane Diterpenoids: [3+2+1] Cycloaddition/Cycloalkenylation Approach

Abstract: The Yu’s Rh-catalyzed [3+2+1] cycloaddition followed by a Pd-mediated 5-endo cycloalkenylation is shown to be a general and powerful approach for efficient construction of the tetracyclic core structure of ent-kaurane diterpenoids. The utility of this strategy was further demonstrated by concise and protecting-group-free total syntheses of ent-1α-hydroxy­kauran-12-one, 12-oxo-9,11-dehydro­kaurene, and 12α-hydroxy-9,11-dehydro­kaurene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 75 publications
0
10
0
2
Order By: Relevance
“…Consequently, we planned to elaborate the required tetracyclic intermediate 10 through a stereoselective intramolecular Michael addition of the ketone 11 , which could in turn be provided by a Cu-mediated conjugate addition of enones 12 and iodide 13 . Encouraged by our synthetic experience with ent -kaurane diterpenoids, the bicyclo[3.2.1]­octane motif 13 would be assembled using Toyota’s Pd-catalyzed cycloalkenylation of a silyl enol ether generated from olefin 14 . The quaternary stereocenter of enone 14 could be built through Stoltz’s Pd-catalyzed decarboxylative allylation reaction of β-keto ester 15 , which could be further derived from the two simple compounds 16 and 17 via an asymmetric S N 2 process.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we planned to elaborate the required tetracyclic intermediate 10 through a stereoselective intramolecular Michael addition of the ketone 11 , which could in turn be provided by a Cu-mediated conjugate addition of enones 12 and iodide 13 . Encouraged by our synthetic experience with ent -kaurane diterpenoids, the bicyclo[3.2.1]­octane motif 13 would be assembled using Toyota’s Pd-catalyzed cycloalkenylation of a silyl enol ether generated from olefin 14 . The quaternary stereocenter of enone 14 could be built through Stoltz’s Pd-catalyzed decarboxylative allylation reaction of β-keto ester 15 , which could be further derived from the two simple compounds 16 and 17 via an asymmetric S N 2 process.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the same strategy was used by the same group in the protecting-group-free total synthesis of entkaurane diterpenoids such as 35 (Scheme 8, b). 56 These three examples demonstrate that the advantages of the conjugate addition methodology employing organozirconium nucleophiles are being recognized by the broader synthetic community. It was also shown that it was possible to tackle several synthetic challenges arising from the use of conventional organometallics.…”
Section: Scheme 7 Synthesis Of Fulvestrant (30)mentioning
confidence: 94%
“…Following previous discussions, we will showcase how sequential C–H functionalizations, radical-based transformations, and a functional group pairing strategy can contribute to our total synthesis of polysubstituted aromatics ( 1 – 4 , Figure ), , ent -kaurane diterpenoids ( 5 – 13 , Figure ), ,, and Lycopodium alkaloids ( 14 – 17 , Figure ), respectively. More importantly, our total synthesis acts as the driving force for the discovery of bioactive compounds as well as a deep understanding of their mechanism of action (MOA).…”
Section: Introductionmentioning
confidence: 90%
“…Since then, the synthesis of an assortment of biologically active ent -kauranes as well as their biological evaluations have been reported by our laboratory (Figure ). ,, …”
Section: Total Syntheses Of Ent-kaurane Diterpenoids Through Radical ...mentioning
confidence: 99%